2018
DOI: 10.1056/nejmoa1803538
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes with PCI Guided by Fractional Flow Reserve

Abstract: In patients with stable coronary artery disease, an initial FFR-guided PCI strategy was associated with a significantly lower rate of the primary composite end point of death, myocardial infarction, or urgent revascularization at 5 years than medical therapy alone. Patients without hemodynamically significant stenoses had a favorable long-term outcome with medical therapy alone. (Funded by St. Jude Medical and others; FAME 2 ClinicalTrials.gov number, NCT01132495 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
418
3
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 688 publications
(498 citation statements)
references
References 20 publications
11
418
3
22
Order By: Relevance
“…[8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events. [8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events. [8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Studies on coronary and carotid artery diseases have also indicated that another hemodynamic index, wall shear stress (WSS), may be involved in evolution of atherosclerotic lesions and the risk of subsequent relevant ischemic events. [8][9][10][11] Studies on coronary and carotid artery diseases have also indicated that another hemodynamic index, wall shear stress (WSS), may be involved in evolution of atherosclerotic lesions and the risk of subsequent relevant ischemic events.…”
mentioning
confidence: 99%
“…At present, invasive FFR is considered the reference standard for guiding coronary revascularization [19], as it is the only diagnostic test shown to improve clinical outcomes and reduce health costs in large, prospective, randomized trials [20-22]. The use of FFR, however, is limited by its invasive nature and cannot always be measured in all vessels of interest because of extreme vessel tortuosity or coronary calcification [23].…”
Section: Introductionmentioning
confidence: 99%
“…The FFR‐based deferral of revascularization is reportedly associated with excellent clinical outcomes under optimal medical therapy. Based on the previous studies, the lesions with FFR value >0.80 have been considered to have no need of revascularization . The prevention of future interventions or cardiac events related to such deferred lesions is of extreme importance after deferral of revascularization.…”
Section: Introductionmentioning
confidence: 99%